2004
DOI: 10.1182/blood.v104.11.2063.2063
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Safety of SB-497115-GR, an Orally Active Small Molecular Weight TPO Receptor Agonist, in Chimpanzees, Rats and Dogs.

Abstract: SB 497115-GR is a small molecular weight Tpo receptor (TpoR) agonist that has properties similar to thrombopoietin (TPO), primarily inducing proliferation and differentiation of megakaryocytes from bone marrow progenitor cells. SB-497115-GR is being developed for the treatment of thrombocytopenias, such as immune thrombocytopenic purpura. In vitro and in vivo studies have demonstrated that SB-497115-GR has very distinct species specificity. SB-497115 or other molecules in this class induced dose dependent STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Eltrombopag is an oral, small molecule, non-peptide TPO-RA. By interacting with the transmembrane domain of the receptor, this drug initiates thrombopoietin-receptor signaling, thereby inducing cell proliferation, differentiation and maturation in the megakaryocytic lineage ( Sellers et al, 2004 ). Romiplostim is a novel peptide molecule that stimulates the megakaryocytopoiesis and increases the platelet count in the same manner as TPO ( Wang et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eltrombopag is an oral, small molecule, non-peptide TPO-RA. By interacting with the transmembrane domain of the receptor, this drug initiates thrombopoietin-receptor signaling, thereby inducing cell proliferation, differentiation and maturation in the megakaryocytic lineage ( Sellers et al, 2004 ). Romiplostim is a novel peptide molecule that stimulates the megakaryocytopoiesis and increases the platelet count in the same manner as TPO ( Wang et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from sequencing studies suggested that thrombopoietin receptor agonists interact with the histine 499 and threonine 496 residues to either change the conformation of the receptor or induce dimerization, resulting in activation of the signal transduction pathways of the thrombopoietin receptor (Erickson-Miller et al 2004b). The species specificity was confirmed in vivo by the lack of effect of eltrombopag on platelet count in rats and dogs, in contrast to chimpanzees (Sellers et al 2004).…”
Section: Preclinical Evidencementioning
confidence: 89%
“…In-vivo eltrombopag was well tolerated in chimpanzees, rats, and dogs at all doses tested (Sellers et al 2004). Phase I data in healthy volunteers have shown that eltrombopag was well tolerated over a 16-day period with no serious adverse events reported.…”
Section: Safety and Tolerabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, an oral thrombopoietin-receptor agonist, eltrombopag (SB-497115) has been shown to stimulate megakaryocyte proliferation and differentiation and to cause dose-dependent increases in platelet counts in chimpanzees and humans. 84 86 It appears that eltrombopag binds the TPO receptor at a distance from the binding site for TPO and appears to initiate signal transduction by a mechanism different from thrombocytopenic growth factors of first generation. 87 Thus, eltrombopag has an additive, and not competitive, effect on platelet production.…”
Section: Management Of Thrombocytopeniamentioning
confidence: 99%